Similarity Measures and Dimensionality Reduction Techniques for Time Series Data Mining - Cassisi, Carmelo; Montalto, Placido; Aliotta, Marco; Cannata, Andrea; Pulvirenti, Alfredo (IntechOpen, 2012)
None